Assessing smoke toxicity of burning combustibles by four expressions for fractional effective dose. (19th June 2020) - Chow, C.L.; Han, S.S.; Han, G.Y.; Hou, G.L.; Chow, W.K.
Summary: Toxicity of smoke generated in a fire is difficult to measure accurately. That is because gas sensors for measuring rapidly varying concentrations of toxic gases are not yet developed. Simple expressions are searched for quick measurement in assessing smoke toxicity practically. Four equations on calculating fractional effective dose (FED) related to toxic effluents were reported in the literature, each based on different assumptions. FED value was proposed to be calculated based on peak carbon monoxide concentration and peak carbon dioxide concentration, and transient carbon monoxide, carbon dioxide, and oxygen concentrations. The four values were compared in this article using literature data on toxic gases from different materials measured by (i) cone calorimeter; (ii) full‐scale burning tests; and (iii) tunnel full‐scale tests. Measured carbon monoxide, carbon dioxide, and oxygen concentrations by standard equipment of oxygen consumption calorimeters were used to calculate the four FED values. It is found that the values of FED based on peak carbon monoxide and carbon dioxide concentrations (denoted as FED2 ) are similar to the average values of FED calculated from the updated equation in the literature using the oxygen consumption calorimeters. Putting the values of FED2 in fire safety design guides is then recommended.